Rates of depression and anxiety in Italian patients with cystic fibrosis and parent caregivers: Implementation of the Mental Health Guidelines. (October 2020) - Graziano, Sonia; Spanò, Barbara; Majo, Fabio; Righelli, Dario; Vincenzina, Lucidi; Quittner, Alexandra; Tabarini, Paola
Abstract: Background: Individuals with chronic respiratory conditions are at-risk for depression and anxiety. In the largest mental health screening study of over 6000 people with cystic fibrosis (CF) and 4000 parent caregivers (TIDES, 2014), rates of symptomatology were two to three times higher than in the general population. International guidelines recommend annual screening of mental health. This is the first study to implement these guidelines in one of the largest CF Centers in Italy. Methods: All individuals with CF, 12 and older (n = 167) and caregivers of children with CF (n = 186), birth to 18, were screened. Health outcome data were also collected (i.e FEV1, BMI, pulmonary exacerbations, CF-related diabetes). Prevalence data and associations between psychological symptoms and health outcomes were examined. Results: A high percentage of patients and parent caregivers reported scored above the clinical cut-off for depression and anxiety (37%–48% of adolescents, 45%–46% of adults, 49%–66% of mothers and fathers). Most scores fell in the mild range, however, over 30% were in the moderate to severe range. Elevations in depression and anxiety were correlated. Adolescents who had more pulmonary exacerbations reported higher anxiety. Adults with recent events of hemoptysis reported higher symptoms of depression. Conclusions: Symptoms of depression and anxiety were elevated in both individuals with CF and parents. Implementation of mental health screening was critical for identifying those in need of psychological interventions. These results strongly suggest that mental health should be integrated into physical health care for those with complex, chronic respiratory conditions, including COPD, PCD. Highlights: Guidelines on Mental Health for cystic fibrosis (CF) were implemented successfully. Use of standardized screening tools: PHQ-9 and GAD-7. Elevated symptoms of depression and anxiety were found in CF patients and parents. Adolescents were at high risk for suicidal ideation: systematic follow-up is needed. Respiratory illness: screening/treatment of depression/anxiety should be integrated.